Prevalence and influencing factors of mild cognitive impairment in the elderly in Songjiang District, Shanghai - Xiuqin CHEN; Zhiyuan LI; Penghao LIU; Junling GAO; Yiling WU; Limei HUANG (环境与职业医学, 2024)
BackgroundWith the aging of China's population, cognitive impairment in the elderly is receiving increasing public attention. Screening and intervention of people with mild cognitive impairment (MCI) are of great significance to prevent and reduce the occurrence of cognitive impairment.ObjectiveTo understand the prevalence and explore potential influencing factors of MCI in the elderly in Songjiang District, Shanghai, and to provide scientific basis for promoting early screening of cognitive impairment and precise intervention of MCI in the elderly in this area. MethodsA cross-sectional study design was adopted. From August to October 2022, using multi-stage random sampling, 1800 elderly residents aged 60 years and above were screened for cognitive impairment in 6 neighborhood/village committees in 6 towns in Songjiang District. The survey questionnaires included a sociodemographic questionnaire, a health status and lifestyle questionnaire, the Instrumental Activities of Daily Living (IADL), the Patient Health Questionnaire (PHQ-9), and the Mini-Mental State Examination (MMSE). Prevalence rates of MCI among the elderly by selected social demographic characteristics, health status, and lifestyle were estimated, and potential influencing factors of MCI were evaluated by binary logistic regression. ResultsA total of 209 elderly residents with MCI and 1591 healthy elderly residents were detected, and the prevalence of MCI in the elderly aged 60 and above was 11.6% in Songjiang District. Being physically active (OR=0.556, 95%CI: 0.399, 0.774) reduced the risk of MCI. Illiteracy (OR=1.810, 95%CI: 1.239, 2.644), primary school education level (OR=3.454, 95%CI: 2.342, 5.092), non-participation in social activities (OR=1.945, 95%CI: 1.360, 2.781), IADL damaged (OR=3.173, 95%CI: 2.137, 4.712), and depression (OR=1.957, 95%CI: 1.112, 3.443) increased the risk of MCI (P＜0.05). ConclusionThe prevalence of MCI among the elderly in Songjiang District is lower than the national average. Educational level, physical activity, participation in social activities, IADL, and depression may be the influencing factors of MCI in the elderly. It is recommended to carry out early screening, early detection, and early intervention for cognitive impairment in the elderly. Improving involvement in physical exercise and increasing participation in social activities are encouraged. Special attention should be paid to the needs of vulnerable groups such as low education level and disabled elderly during a community MCI intervention program.